THE ROLE OF INFORMATION TECHNOLOGIES IN THE EDUCATIONAL PROCESS OF THE UNIVERSITY IN THE ASPECT OF TEACHING RUSSIAN AS A FOREIGN LANGUAGE (Proceedings of International Conference on Scientific Research in Natural and Social Sciences, 2023)
The article explains the role of information technology in the educational process of higher educational institutions in the aspect of training of foreign nationals Russian as a foreign language. Reveals the potential of information technology in the aspect of the efficiency of the formation of multicultural value orientations in teaching Russian as a foreign language. The correlation between the formation of valuable orientations of multicultural competency and conduct of foreign students in the university environment, socio-cultural, mediated for their context of learning Russian as a foreign language.